Seasonal Determination of Antibiotic-Resistant Microorganisms and Ciprofloxacin Residues in Pork and Chicken Meats Collected from Fresh Markets in Chiang Mai, Northern Thailand - Sirikwan Dokuta; Sumed Yadoung; Sayamon Hongjaisee; Phadungkiat Khamnoi; Sirinya Manochomphu; Bajaree Chuttong; Surat Hongsibsong (Foods)
Antibiotic-resistant bacteria are usually found in food-producing animals worldwide. Ciprofloxacin, an antibiotic, can lead to antibiotic residues in food products, posing health risks to consumers and contributing to the development of antimicrobial resistance. Foodborne illnesses occur when adequate attention is not paid to food hygiene and safety, raising the potential for resistant bacteria to spread to humans through the food chain. This study aims to determine the presence of antibiotic-resistant organism contamination and ciprofloxacin residue in raw pork and chicken. Forty-three pork and 33 chicken meat samples were collected from fresh markets in Chiang Mai, Thailand. Antibiotic-resistant organisms were detected by microbial culture and identified by MALDITOF-MS. The antimicrobial sensitivity tests were used to confirm antibiotic resistance. The ciprofloxacin was detected by using an immunochromatographic-based test kit for screening. The results found Extended Spectrum β-lactamase (ESBL)-producing E. coli and K. pneumoniae were detected at 46.51% and 9.30% in pork and 69.70% and 6.06% in chicken meat samples, respectively. Moreover, ciprofloxacin residues were detected in nine samples (11.84%). Based on this study’s findings, the people who are involved in the food chain must be concerned about food safety and food hygiene.